Performing Corporate Culture: Analysing Meta-Narratives and Online Interactivity Through Quigital. - Britton, Eliot; Arbez, David; Hart, Patrick; McPhillips, Kevin (Contemporary Music Review, 2023)
Home Comfort Advisor is a collaborative composition for online choir, presented by the fictional corporation 'Quigital'. This paper details the work's co-opting of corporate aesthetics, analysis, productivity, design strategies and their implications in musical language, collaboration, performer agency and audience reception. The resulting choir performance masquerades as an interactive online product launch, making unconventional analytical demands on individual choir members as singers, community members, distributed decision makers and content creators. To manage the logistical challenges presented by an interdisciplinary collaboration featuring 70 agents and a creative development team, linear approaches to composition were replaced by a modified iterative design loop. (Collaborative creation ⇒ analysis ⇒ (re)-interpretation ⇒ interactive audience engagement: repeat/deploy:). More specifically, this paper examines emergent materials, structures and processes used to amplify collaboration. Home Comfort Advisor's deeply embedded corporate aesthetic and technological infrastructure reveals novel interactions between the score, text, code, design assets, analysist and performer. An analysis of the non-linear, collaborative relationships provides a model for creating similar data-driven, interdisciplinary collaborations. Quigital's manipulation of a mutually understood code hidden in plain sight approaches what Limor Shifman refers to as hypersignification. This cultivation of technologically amplified, collaborative metanarrative lies at the heart of Quigital's success and its ability to be both approachable, subversive and deeply disturbing.